Incorporation of aluminum oxide in the formulation os pastes for building materials (2018)
This work analyzes the influence of aluminum oxide with a particle size of less than 75 μm on the behavior in a clay, when it is mixed with this material at 10% by weight. It is observed how it influences the different stages of the manufacturing process and its effect on structural, mechanical and tribological properties. In previous works it has been used in different percentages increasing the mechanical resistance. For this work a composition was formulated using clay of high plasticity and making the conforming by the extrusion method. The results show the efficacy and efficiency of this material and its mechanism of action, showing increases in mechanical properties and a decrease in porosity. In addition to improving its tribological properties, granting to the products added value and the possibility to be suitable manufacture materials to be used in environments of intense pedestrian traffic or in industrial environments.